Beginning J2ME From Novice to Professional - Li, Sing; Knudsen, Jonathan (Apress : Imprint: Apress, 2005)
Have you thought about building games for your cell phone or other wireless devices? Whether you are a first-time wireless Java developer, or an experienced professional Beginning J2ME, Third Edition brings exciting wireless and mobile Java application development right to your door! This book will empower you with numerous topics: sound HTTPS support, user interface API enhancements, sound/music API, a Game API, 3D graphics, and Bluetooth. Further, this book is easy to read and includes many practical, hands-on, and ready-to-use code examples. You will not be disappointed.